Idealization of the Past at the Beginning of the 19th Century in Lithuania - Genzelis, Bornislovas (Problemos, 1968)
Idealization of the past is characteristic of many nations in Central and South-East Europe of that time. The article analyses the causes and theoretical sources of this conception in Lithuania; it shows that the conception was called forth by the requirements of struggle against social and national oppression. The author stresses the opinion that the phenomenon should be treated comprehensively on the basis of Marxist methodology.